Every vow you break eaudiobook A novel. - Swanson, Peter (2021)
A bride's dream honeymoon becomes a nightmare when a man with whom she's had a regrettable one-night stand shows up in this electrifying psychological thriller from the acclaimed author of Eight Perfect Murders. Abigail Baskin never thought she'd fall in love with a millionaire. Then she met Bruce Lamb. He's a good guy, stable, level-headed, kind—a refreshing twist from her previous relationships. But right before the wedding, Abigail has a drunken one-night stand on her bachelorette weekend. She puts the incident—and the sexy guy who wouldn't give her his real name—out of her mind, and now believes she wants to be with Bruce for the rest of her life. Then the mysterious stranger suddenly appears—and Abigail's future life and happiness are turned upside down. He insists that their passionate night was the beginning of something much, much more. Something special. Something real—and he's tracked her down to prove it. Does she tell Bruce and ruin their idyllic honeymoon—and possibly their marriage? Or should she handle this psychopathic stalker on her own? To make the situation worse, strange things begin to happen. She sees a terrified woman in the night shadows, and no one at the resort seems to believe anything is amiss... including her perfect new husband.